The application of polyamines and self-incompatibility control substance on yield indices and qualitative traits of apple cv ‘Red Delicious’ - Sayyad-Amin, Pegah (2018)
Among the main problems of some temperate fruit species, such as the apple tree (Malus domestica), are the poor set of fruits and low production. Polyamines and Self-Incompatibility Control Substances (SICS), involving mineral nutrients such as manganese and boron, are the major chemical compounds used to reduce these problems. The aim of this study was to use popular polyamines putrescine (Put) at 0.1, 0.25 mM, spermine (Spm) and spermidine (Spd) both at 0.05, 0.25 mM and SICS at 1, 2 mg L-1, alone or with cotton coverage bags and control to show the effects of these chemical compounds on yield indices and qualitative traits of apple (Malus domestica) cv ‘Red Delicious’. Results showed that Spd (0.25 mM) and SICS (1 mg L-1) had higher effect on yield per weight and per fruit number, final fruit set and ISI, but Spd (0.25 mM) decreased final drop. Put (0.1 mM + ccb), Spd (0.25 mM) and SICS (2 mg L-1 + ccb) were the most suitable treatments in order to increase the qualitative characteristics.